Two new species of Mimosa (Fabaceae) endemic to Bolivia - Atahuachi, M; Hughes, C (2006)
Two new species of Mimosa are described: M. woodii (sect. Mimosa), from the central Andean valleys of Bolivia, and M. suberosa (sect. Habbasia), from Serranía Huanchaca in the Noel Kempff National Park in the north east of Santa Cruz Department in eastern Bolivia. The affinities of each are discussed, their distributions mapped, and both species are illustrated. © 2006, by The New York Botanical Garden Press.